Plant and Animal Imagery in the Churches of Chucuito in the Late Colonial Period - Bailey, Gauvin Alexander (2025)
The architectural sculpture of the so-called ‘Mestizo Baroque’ or ‘Andean Hybrid Baroque’ churches of southern Peru and Bolivia has fascinated – and polarized – scholars of Latin American colonial art for precisely a century, particularly the degree to which it reflects indigenous sensibilities and styles. Scholars from Ángel Guido and Martín Noel to Teresa Gisbert and the present reviewer have paid particular attention to the significance of the rich assortment of flowers, other plants, birds, and animals that animate these facades, some of them originating in European Christian iconography and others clearly of Andean and Amazonian origin.